Análise inelástica de pórticos planos considerando a plasticidade distribuída e o efeito das tensões residuais nos perfis estruturais de aço - Andreia Cristina Barroso Almeida (2006)
A geometrically exact finite element formulation to consider material and geometric nonlinearities of steel plane frames is presented. The distributed-plasticity analysis for members with rigid-pinned joints and residual stresses due manufacturing process are also included. An overview of Advanced Analysis in order to define the desirable attributes for the development of an Advanced Inelastic Analysis model is outlined. A general theory considering self equilibrated residual stresses is developed based on updated Lagrangian formulation. The Corrotacional technique is used to obtain the elements tangent stiffness matrix. The abilities for analyzing pin-ended joint members, residual stresses in webs, different nodal loads with different increments and factored combinations were added to the original computational program version presented by LAVALL (1996). The frame element, made up of layers, enable to identify the plastic region through the cross section and in the member length for any kind of residual stresses. A preprocessor is developed looking for friendly users interface and automatic inputs dates. Finally, spreading of plasticity, residual stresses and explicit geometric imperfection effects were analyzed in the examples presented. The strengths predicted by the proposed formulation are compared with those predicted by the NBR 8800(2006) review project, proving the efficiency of this approach as Advanced Analysis method.